Delineating a novel metabolic high triglycerides-low waxes syndrome that affects lipid homeostasis in meibomian and sebaceous glands. (October 2020) - Butovich, Igor A.; Suzuki, Tomo
Abstract: Meibomian glands that are embedded in tarsal plates of human eyelids, and sebaceous glands found in the skin, including that of eyelids, are two related types of holocrine glands that produce lipid-rich secretions called meibum and sebum. Pervasive ocular disorders, such as Meibomian gland dysfunction and dry eye, have been linked to changes in the lipid composition of meibum. However, in most described cases the changes were either small, or random, or insufficiently characterized on the molecular level. Here, we present results of comprehensive lipidomic analyses of meibum, tears and sebum of a patient whose secretions were highly abnormal (abnormal meibum, tears and sebum, or AMTS, patient). The lipidomes were characterized on the level of individual lipid species using ultra-high performance liquid chromatography and high resolution mass spectrometry. The major differences between the AMTS patient and normal age- and gender-matched subjects included, among others, severely diminished pools of normal meibomian lipids such as wax esters and cholesteryl esters in meibum and tears, a 2x increase in total cholesteryl esters to wax esters ratio, their skewed molecular profiles, a ~3x increase in free cholesterol to cholesteryl esters ratio, and, most importantly, a 20x to 30x increase in the triglicerides fraction over the norm. Sebum of the AMTS patient was also highly abnormal lacking major wax esters. Notably, the routine blood lipid panel test of the AMTS patient showed no abnormalities. The data imply that the AMTS patient had a severe, previously unreported, metabolic disorder that affected meibogenesis in Meibomian glands and sebogenesis in sebaceous glands. This is, to the best of our knowledge, a first observation of the condition that we have termed High Triglycerides/Low Waxes (HTLW) syndrome. Highlights: A severe metabolic disorder affects lipid homeostasis in Meibomian glands and tears. Triglycerides (TAG) were 20x to 30x over the normal levels. The increase in TAG led to a decline in wax esters (WE) and cholesteryl esters (CE). Free cholesterol in abnormal meibum was increased 3x over the normal levels. The disorder also affected sebaceous lipids, specifically lowering their WE/TAG ratio.